2006
DOI: 10.1016/j.annemergmed.2006.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Modified N95 Mask Delivers High Inspired Oxygen Concentrations While Effectively Filtering Aerosolized Microparticles

Abstract: An N95 mask can be modified to administer a clinically equivalent FiO2 to a nonrebreathing mask while maintaining its filtration and isolation capabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 16 publications
1
24
0
1
Order By: Relevance
“…Most has been laboratory based, 7,8 meaning that work conditions were approximated by walking on a treadmill and/or involved young, healthy subjects. 9,10 Only 1 study has examined long-term N95 use among health care personnel in an actual work setting, 11 and that study only assessed perceived intolerance. In addition to physiologic factors, researchers indicate that subjective symptoms/conditions, such as perceived comfort, headaches, or difficulty communicating with patients, may affect health care personnel's tolerance of long-term N95 use.…”
mentioning
confidence: 99%
“…Most has been laboratory based, 7,8 meaning that work conditions were approximated by walking on a treadmill and/or involved young, healthy subjects. 9,10 Only 1 study has examined long-term N95 use among health care personnel in an actual work setting, 11 and that study only assessed perceived intolerance. In addition to physiologic factors, researchers indicate that subjective symptoms/conditions, such as perceived comfort, headaches, or difficulty communicating with patients, may affect health care personnel's tolerance of long-term N95 use.…”
mentioning
confidence: 99%
“…This is because transmissibility could have been increased by an inadequate use of protective personal equipment (PPE) in early cases; 11,26 NIV equipment has evolved since 2003-4, and there have been subsequent experimental studies that have investigated air flows around oxygen masks and during NIV. [27][28][29][30] These studies used human simulator models or normal subjects mimicking respiratory distress. Hui et al 28,31 have carried out a series of experimental studies analysing particle spread from NIV and oxygen masks, 32 using smoke particles as a proxy of droplets in expired air.…”
Section: Chaptermentioning
confidence: 99%
“…In that event, a mask protecting the patient from the environment, in addition to source containment and supplemental oxygen for the infected patient, would be needed. Although such a device is not currently available, Mardimae et al (32) have demonstrated that an N95 mask may be modified to permit supplemental oxygen administration without loss of filtration and isolation efficacy. A N95 non-rebreather mask, the ISO-O 2 Oxygen Mask (Viasys), has been approved for use by Health Canada and European licensing bodies (Fig.…”
Section: Masks For Contagious Patientsmentioning
confidence: 98%